Characterizing the interindividual postexercise hypotension response for two order groups of concurrent training in patients with morbid obesity - Álvarez, Cristian; Guede-Rojas, Francisco; Ramírez-Campillo, Rodrigo; Andrade, David C.; Vásquez-Gómez, Jaime; Rodríguez-Rodríguez, Fernando; Ciolac, Emmanuel Gomes; Caamaño-Navarrete, Felipe; Delgado-Floody, Pedro (Frontiers in Physiology, 2022)
Background: Postexercise hypotension (PEH) is a common physiological phenomenon occurring immediately after endurance training (ET), resistance training (RT), and ET plus RT, also termed concurrent training (CT); however, there is little knowledge about the interindividual and magnitude response of PEH in morbidly obese patients. Aim: The aims of this study were (1) to investigate the effect of CT order (ET + RT vs. RT + ET) on the blood pressure responses; 2) characterize these responses in responders and nonresponders, and 3) identify potential baseline outcomes for predicting blood pressure decreases as responders. Methods: A quasi-experimental study developed in sedentary morbidly obese men and women (age 43.6 ± 11.3 years; body mass index [BMI] ≥40 kg/m2) was assigned to a CT group of ET plus RT (ET + RT; n = 19; BMI 47.8 ± 16.7) or RT plus ET order group (RT + ET; n = 17; BMI 43.0 ± 8.0). Subjects of both groups received eight exercise sessions over four weeks. Primary outcomes include systolic (SBP), diastolic (DBP), mean arterial pressure [MAP], heart rate at rest [HR], and pulse pressure [PP] measurements before and after 10 min post-exercise. Secondary outcomes were other anthropometric, body composition, metabolic, and physical fitness parameters. Using the delta ∆SBP reduction, quartile categorization (Q) in “high” (Rs: quartile 4), “moderate” (MRs: quartile 3), “low” (LRs: quartile 2), and “nonresponders” (NRs: quartile 1) was reported. Results: Significant pre–post changes were observed in ET + RT in session 2 for SBP (131.6 vs. 123.4 mmHg, p = 0.050) and session 4 (131.1 vs. 125.2 mmHg, p = 0.0002), while the RT + ET group showed significant reductions in session 4 (134.2 vs. 125.3 mmHg, p < 0.001). No significant differences were detected in the sum of the eight sessions for SBP (∑∆SBP) between ET + RT vs. RT + ET (−5.7 vs. −4.3 mmHg, p = 0.552). Interindividual analyses revealed significant differences among frequencies comparing Q1 “NRs” (n = 8; 22.2%), Q2 “LRs” (n = 8; 22.2%), Q3 “MRs” (n = 9; 25.0%), and Q4 “HRs” (n = 11; 30.5%), p < 0.0001. Quartile comparisons showed significant differences in SBP changes (p = 0.035). Linear regression analyses revealed significant association between ∑∆SBP with body fat % (β –3.826, R2 0.211 [21.1%], p = 0.031), skeletal muscle mass [β –2.150, R2 0.125 (12.5%), p = 0.023], fasting glucose [β 1.273, R2 0.078 (7.8%), p = 0.003], triglycerides [β 0.210, R2 0.014 (1.4%), p = 0.008], and the 6-min walking test [β 0.183, R2 0.038 (3.8%), p = 0.044]. Conclusion: The CT order of ET + RT and RT + ET promote a similar ‘magnitude’ in the postexercise hypotensive effects during the eight sessions of both CT orders in 4 weeks of training duration, revealing “nonresponders” and ‘high’ responders that can be predicted from body composition, metabolic, and physical fitness outcomes.